Development of a 17-Plex of Penta- and Tetra-Nucleotide Microsatellites for DNA Profiling and Paternity Testing in Horses - Luttman, Andrea M.; Komine, Misa; Thaiwong, Tuddow; Carpenter, Tyler; Ewart, Susan L.; Kiupel, Matti; Langohr, Ingeborg M.; Venta, Patrick J. (Frontiers in Veterinary Science, 2022)
Tetranucleotide and pentanucleotide short tandem repeat (hereafter termed tetraSTR and pentaSTR) polymorphisms have properties that make them desirable for DNA profiling and paternity testing. However, certain species, such as the horse, have far fewer tetraSTRs than other species and for this reason dinucleotide STRs (diSTRs) have become the standard for DNA profiling in horses, despite being less desirable for technical reasons. During our testing of a series of candidate genes as potentially underlying a heritable condition characterized by megaesophagus in the Friesian horse breed, we found that good tetraSTRs do exist in horses but, as expected, at a much lower frequency than in other species. Using a series of efficient methods developed in our laboratory for the production of multiplexed tetraSTRs in other species, we identified a set of tetra- and pentaSTRs that we developed into a 17-plex panel for the horse, plus a sex-identifying marker near the amelogenin gene. These markers were tested in 128 horses representing 16 breeds as well as crossbred horses, and we found that these markers have useful genetic variability. Average observed heterozygosities (Ho) ranged from 0.53 to 0.89 for the individual markers (0.66 average Ho for all markers), and 0.62 to 0.82 for expected heterozygosity (He) within breeds (0.72 average He for all markers). The probability of identity (PI) within breeds for which 10 or more samples were available was at least 1.1 x 10-11, and the PI among siblings (PIsib) was 1.5 x 10-5. Stutter was less than or equal to 11% (average stutter for all markers combined was 6.9%) compared to the more than 30% typically seen with diSTRs. We predict that it will be possible to develop accurate allelic ladders for this multiplex panel that will make cross-laboratory comparisons easier and will also improve DNA profiling accuracy. Although we were only able to exclude candidate genes for Friesian horse megaesophagus with no unexcluded genes that are possibly causative at this point in time, the study helped us to refine the methods used to develop better tetraSTR multiplexed panels for species such as the horse that have a low frequency of tetraSTRs.